QUESTIONS FOR CHARACTER CREATION IN MODERN SHORT STORIES (TAMADDUN NURI JURNALI, 2024)
In the article, one of the widely studied topics in literary studies is expressed some comments on the question of literary character. An attempt was made to express reasonable opinions on issues such as its types and difficulties of creation, the writer's artistic skills, the role of his style in this regard, and the importance of character in epic genres. The topic was discussed during the analysis of the stories of Abdukayum Yoldosh and Lukman Borikhon, two skilled representatives of Uzbek prose of the independence period. Analysis of their creative approach to character creation is provided. In justifying the opinions, the theoretical views of famous literary scholars and some examples of world literature were referred to.